The impact of questioning and semantic map in pre-reading stage on EFL gifted high school students' reading comprehension: a comparative study : - Trần, Thị Thanh Thủy (Trường Đại học Cần Thơ, 2018)
This thesis introduce about impact of questioning and semantic map in pre-reading stage on EFL gifted high school students' reading comprehension: a comparative study.